Sentinel Lymph Node Mapping with Gamma Probe in Carcinoma of Breast: Initial Experience in Evercare Hospital Dhaka (Bangladesh Journal of Nuclear Medicine, 2022)
Background: The sentinel lymph node (SLN) is the first draining node from a cancer-bearing area and therefore can manifest metastasis. In breast cancer SLN has been shown to predict the axillary nodal stage. Axillary dissection provides information determining prognosis and need for adjuvant therapy but often carries certain morbidities. Our aim was to determine the feasibility of detecting the SLN and whether the SLN accurately predicts the axillary status.Materials and Methods: Twelve patients having mean age of 40.5 ± 10.9 years, ranging from 28 to 56 years with stage I and II breast cancer and non-palpable axillary nodes from November 2016 to December 2018 were included in this study. The sentinel node was detected with Tc-99m-labelled nano colloid (radiotracer). Dual Head SPECT Gamma Camera and Gamma Probe was used in the same sitting for identification and surface marking of the SLN. Surgical resection of SLN was done followed by frozen section biopsy.Results: The tumor size ranged from